A Grief and Loss Scene That Occurred in Southeast Asia - Nurhaliza, Siti; Agustina, Rina; Adventus, Adventus; Alfaroji, Muhammad Arif; Alrefi, Alrefi; Minarsi, Minarsi; Lubis, Anissa Rachmawati; Sahendra, Yani (Journal of Society Counseling, 2024)
Grief is an emotion triggered by an event, experience or situation that is painful and disappointing. This research was conducted to gain a deeper understanding of how grief and loss are understood and experienced by people in Southeast Asia. In this study, the researcher uses a qualitative approach to literature study research, where researchers searched for literature articles related to Grief or grief that occurred in Southeast Asia in the 2017–2023 time span. The results showed that grief and loss are related to each other, the grief experienced by individuals is of several types, such as complicated grief and uncomplicated grief. Showing the reaction to grief from individuals, it is characterized by crying and showing an attitude of disbelief towards something that happened. In addition, the causes of grief experienced by individuals, especially in Southeast Asia, are due to the sudden death of parents, the Coronavirus outbreak which caused many deaths, divorce, and the diagnosis of a terminal illness in a person. However, people in Southeast Asia who experience grief and loss also exhibit diverse ways of coping with their grief such that some individuals successfully move through the phases of their grief, while others remain in the long-term grief phase.